2021
DOI: 10.1016/j.gpb.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

SLM2 Is a Novel Cardiac Splicing Factor Involved in Heart Failure due to Dilated Cardiomyopathy

Abstract: Alternative mRNA splicing is a fundamental process to increase the versatility of the genome. In humans, cardiac mRNA splicing is involved in the pathophysiology of heart failure. Mutations in the splicing factor RNA binding motif protein 20 (RBM20) cause severe forms of cardiomyopathy. To identify novel cardiomyopathy-associated splicing factors, RNA-seq and tissue-enrichment analyses were performed, which identified up-regulated expression of Sam68-Like mammalian protein 2 (SLM2) in the left ventricle of dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Intron retention (IR) is a typical exemplar of regulated splicing which has been, until recently, largely overlooked in mammalian organisms (Jacob and Smith, 2017). In heart failure patients, increased IR of essential cardiac constituents such as Titin, is hypothesized to be involved in the cellular stress response (Boeckel et al, 2021), which would be consistent with our observations. There is also growing evidence that antisense-mediated gene regulation is involved in different pathophysiological contexts, including heart disease (Luther, 2005;Zinad et al, 2017;Celik et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Intron retention (IR) is a typical exemplar of regulated splicing which has been, until recently, largely overlooked in mammalian organisms (Jacob and Smith, 2017). In heart failure patients, increased IR of essential cardiac constituents such as Titin, is hypothesized to be involved in the cellular stress response (Boeckel et al, 2021), which would be consistent with our observations. There is also growing evidence that antisense-mediated gene regulation is involved in different pathophysiological contexts, including heart disease (Luther, 2005;Zinad et al, 2017;Celik et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Intron retention (IR) occurs when an intron is transcribed into pre-mRNA and remains in the final mRNA. Only recently has IR become of interest due to its associations with complex diseases (Zhang et al, 2020;Boeckel et al, 2021). Interestingly, among differentially expressed transcript markers, we found across the infarct and border zones 65 distinct IR transcripts, compared to 1,612 in the remote zones, corresponding to an odds ratio of 1.73 (p-value 0.008).…”
Section: Scnast Reveals the Spatial Isoform Diversity Of The Myocardi...mentioning
confidence: 74%
“…The pipeline uncovered many potential candidate genes, both known and novel in their relation to cardiomyopathy. The three genes with an imbalance in 79 of the samples, ABLIM1, TNNT2, and AKAP13, all have known isoforms due to alternative splicing [12][13][14] . Thus, these genes, as well as other commonly imbalanced genes in the dataset, might be differentially spliced and therefore showing allelic imbalance in people with DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Most genes only showed significant imbalance in one or a few of the subjects, whereas only a few genes showed imbalance in more than half of the subjects. The three genes with the highest shared imbalance showed imbalance in 79 of the samples; ABLIM1, TNNT2, and AKAP13, all of which have known isoforms resulting from alternative splicing [12][13][14] . In concordance with previous studies, the genes with at least one significantly imbalanced SNP showed significant enrichment for eQTLs, p = 6.9E −3 , and sQTLs, p = 5.7E −610 .…”
mentioning
confidence: 99%
“…A growing list of additional splicing factors have been identified that can also regulate titin splicing in the heart. These factors include RBM24 ( Liu et al, 2019 ), PTB4 ( Dauksaite and Gotthardt, 2018 ), SLM2 ( Boeckel et al, 2022 ), and RBPMS ( Gan et al, 2023 ). Importantly, studies have only provided evidence for the regulation of select exons in titin for each of these factors and, apart from RBPMS ( Gan et al, 2023 ), none of these factors have been shown to significantly switch titin size ( Dauksaite and Gotthardt, 2018 ; Liu et al, 2019 ; Boeckel et al, 2022 ).…”
Section: Functional Roles Of Titin In Cardiac Musclementioning
confidence: 99%